2015
DOI: 10.1093/mutage/gev051
|View full text |Cite
|
Sign up to set email alerts
|

Somatic-cell mutation induced by short exposures to cigarette smoke in urate-null, oxidative stress-sensitive Drosophila

Abstract: We previously reported that a urate-null strain of Drosophila is hypersensitive to cigarette smoke (CS), and we suggested that CS induces oxidative stress in Drosophila because uric acid is a potent antioxidant. Although the carcinogenic risk of CS exposure is widely recognized; documentation of in vivo genotoxic activity of environmental CS, especially gaseous-phase CS, remains inconclusive. To date, somatic-cell mutations in Drosophila resulting from exposure to CS have not been detected via the somatic muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The roles of uric acid as an antioxidant and radical scavenger have been widely recognized in vitro and in several organisms, including primates [ 1 6 ]. Previously, we reported that ECS and paraquat induced mutations in a urate-null mutant Drosophila strain, but not in wild-type Drosophila [ 11 ]. We showed that ROS were produced in the larval bodies exposed to ECS, which suggested that ROS are implicated in the mutagenicity of ECS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The roles of uric acid as an antioxidant and radical scavenger have been widely recognized in vitro and in several organisms, including primates [ 1 6 ]. Previously, we reported that ECS and paraquat induced mutations in a urate-null mutant Drosophila strain, but not in wild-type Drosophila [ 11 ]. We showed that ROS were produced in the larval bodies exposed to ECS, which suggested that ROS are implicated in the mutagenicity of ECS.…”
Section: Discussionmentioning
confidence: 99%
“…The Oregon-R and y v ma-l strains were kindly provided by Dr. H. Ryo (Osaka University, Suita, Japan). The y v ma-l; mwh strain was developed in our laboratory [ 11 ]. Both the ry 506 and mwh, ry 506 strains were obtained from the Drosophila Genomics and Genetic Resources Center at Kyoto Institute of Technology (Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the responses of insects to different sources of smoke pollution can be studied and summarized. For example, when Drosophila melanogaster are exposed to cigarette smoke for over six hours, there is an increasing possibility of gene mutagenesis ( Uchiyama et al 2016 ). Some butterfly species can display mortality when exposed to high-level air pollution induced by coal power plants, like Thecla betulae (Lepidoptera: Lycaenidae) ( Corke 1999 ).…”
Section: Discussionmentioning
confidence: 99%